Homologous autoimplantation; an effective modality in the treatment of multiple warts; a non-randomized interventional study at a tertiary care hospital in North-Eastern India - Chhangte, Mary Zothanpuii; Verma, Shikha; Marak, Anita; Thakur, Binod Kumar (International Journal of Research in Dermatology, 2021)
Background: Although there are multiple treatment options, viral warts are known for their persistence and recurrence. Surgical autoimmunization is believed to work by inducing a cell-mediated immune response to clear verrucae-inducing human papillomavirus from the body. Methods: The study was conducted as a non-randomized interventional study at a Tertiary Care Hospital in North Eastern India. All patients above 18 years of age attending the Dermatology Clinic who were diagnosed as having multiple warts were included in the study. Autoinoculation was performed after taking patient’s consent and patients were followed up monthly for 3 months. Photographs were taken at each visit to have an objective comparison, and results assessed at the end of 3 months. Results: Out of 65 patients, 18 patients were lost to follow up and 47 patients completed the study. Complete resolution was found in 17 patients and 10 patients had partial resolution at the end of the study. The response was higher in those from the rural population compared to those from the urban areas and also in those with a short duration of the disease. Conclusions: Autoinoculation is an effective and safe treatment modality especially in palmoplantar warts. Early intervention is required as the response was better in patients with a short duration of the disease, which was statistically significant. Further studies should be done in other clinical variants of warts to see for significant response.